The relationship between gambling advertising and gambling attitudes, intentions and behaviours: a critical and meta-analytic review. (February 2020) - Bouguettaya, Ayoub; Lynott, Dermot; Carter, Adrian; Zerhouni, Oulmann; Meyer, Silke; Ladegaard, Isak; Gardner, John; O'Brien, Kerry S
Abstract : Gambling advertising has become ubiquitous in westernised countries in the last two decades, yet there is little understanding of the relationship between exposure to gambling advertising and gambling attitudes, intentions and behaviour. We conduct a critical and meta-analytic review of the past two decades of empirical research. The research suggests a positive association between exposure to gambling advertising and gambling-related attitudes, intentions and behaviour. The association is greatest for gambling behaviour. There is some evidence for a dose-response relationship. The quality and breadth of research on gambling advertising are weaker than those in comparable areas (e.g., alcohol, tobacco), with an absence of longitudinal and experimental studies. Gaps in, and methodological problems with, the field are discussed, and research directions recommended.